2020
DOI: 10.1063/5.0021849
|View full text |Cite
|
Sign up to set email alerts
|

Deducing transport properties of mobile vacancies from perovskite solar cell characteristics

Abstract: The absorber layers in perovskite solar cells possess a high concentration of mobile ion vacancies. These vacancies undertake thermally activated hops between neighbouring lattice sites. The mobile vacancy concentration N 0 is much higher and the activation energy E A for ion hops is much lower than is seen in most other semiconductors due to the inherent softness of perovskite materials. The timescale at which the internal electric field changes due to ion motion is determined by the vacancy diffusion coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 61 publications
(79 reference statements)
4
35
0
Order By: Relevance
“…Motivated by the successful reproduction of experimental observation by the simulations, we varied the ion density (Figure 1d) and diffusion coefficient (Figure 1e) to study the effect on the JV curves and the PCE difference between the forward and reverse scan. As discovered earlier by others, [ 44 ] we see that the hysteresis is absent at fast and slow scan speeds. Moreover, the timescale at which the maximum JV hysteresis (which we call “peak hysteresis”) occurs, appears to depend primarily on the ion diffusion coefficient (the larger D ion the higher the scan speed to resolve the maximum hysteresis) and to a lesser degree on the ion density.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Motivated by the successful reproduction of experimental observation by the simulations, we varied the ion density (Figure 1d) and diffusion coefficient (Figure 1e) to study the effect on the JV curves and the PCE difference between the forward and reverse scan. As discovered earlier by others, [ 44 ] we see that the hysteresis is absent at fast and slow scan speeds. Moreover, the timescale at which the maximum JV hysteresis (which we call “peak hysteresis”) occurs, appears to depend primarily on the ion diffusion coefficient (the larger D ion the higher the scan speed to resolve the maximum hysteresis) and to a lesser degree on the ion density.…”
Section: Resultssupporting
confidence: 87%
“…The results demonstrate a maximum amplitude of the hysteresis at scan speeds of 10 V s −1 (or 100 ms per scan), while the hysteresis is absent at lower and significantly higher scan speeds. [ 44 ] As we will demonstrate in detail in this manuscript, the PCE at the fastest scan speeds is approximately equal to the PCE in the absence of mobile ions. Hence, one can use the point at high scan speeds where the forward and reverse scan merge again to estimate the “ion‐free” PCE and the difference between the steady‐state PCE (i.e., at low scan speed) and the fast scan to determine the losses due to the mobile ions.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In contrast, a lower scan rate can provide more time for ion vacancies to migrate. [36] This explains the downward shift of the rapid changing region with increasing E a .…”
Section: Scan Rate [Vsmentioning
confidence: 87%
“…Recent modeling studies on PSC devices have mainly focused on (1) the mechanism of ion accumulation, (2) how ion accumulation affects hysteresis, and (3) the effects of different factors of perovskite on hysteresis 23 , 23 27 . To simplify the model, some assumptions have been made about the transport layer of carrier injection with heavily acceptor/donor doping in previous works 28 33 . However, existing doping techniques cannot be applied in the organic transport layer, and some studies have shown that the organic material is an essential factor in the hysteresis behavior 34 .…”
Section: Introductionmentioning
confidence: 99%